Patient-Reported Financial Burden Following Stereotactic Body Radiation Therapy for Localized Prostate Cancer - Sholklapper, Tamir N.; Creswell, Michael L.; Payne, Alexandra T.; Markel, Michael; Pepin, Abigail; Carrasquilla, Michael; Zwart, Alan; Danner, Malika; Ayoob, Marilyn; Yung, Thomas; Collins, Brian; Kumar, Deepak; et al. (Frontiers in Oncology, 2022)
Introduction and Objectives In patients with localized prostate cancer, 5-fraction, stereotactic body radiation therapy (SBRT) has been found to offer comparable oncologic outcomes and potential for improved treatment compliance compared to conventional, 40-plus fraction radiation therapy (RT). Recent studies of oncologic patient experiences have highlighted both the impact of therapy-associated financial toxicity (FT) on treatment adherence and health-related quality of life (HRQOL). Methods A cross-sectional assessment of FT after SBRT was performed using the 12-item COST questionnaire. The total questionnaire score (range 0–44) was used to evaluate the FT grade (0–3), with a higher COST value representing lower grade. The patient zip code was used to approximate the distance from the index hospital. Univariate and multivariate analyses of the average COST score (0–4) are performed. Results The response rate was 57.5% (332 of 575 consented patients) with 90.7%, 8.2%, and 1.1% experiencing grade 0, 1, and 2 FT, respectively, with no grade 3. Unemployment or disability, non-white race, low income, and concurrent hormonal therapy were associated with a statistically significant worse FT (lower COST value) on univariate and multivariate analyses (p < 0.05). Education level and insurance status significant were evaluated on univariate analysis only. There was a non-statistically significant difference in age, marital status, time since treatment, and distance from the index hospital. Conclusions SBRT was associated with low FT. However, statistically significant socioeconomic disparities in FT remain despite ultra-hypofractionated treatment.